Long-term outcomes of multi-context childhood poverty: Evidence from long panel data from Indonesia - Jiaying Chen; Rhea Molato; Albert Park; Donnie-Paul Tan (Asian Development Bank (ADB), 2026)
Which poverty context matters for long-term outcomes-family or community, economic or social? We construct a measure of poverty along these dimensions and analyze individual-level longitudinal data spanning 21 years in Indonesia to examine the long-term outcomes associated with different types of deprivation experienced in childhood. We find that adverse outcomes in adulthood are associated not only with growing up in a poor family but also in a poor community. Family poverty generally has a stronger influence than community poverty, except for health and life satisfaction, which are shaped more by the community. We also find that both economic and social domains matter, with the economic domain's influence being stronger. Girls' education suffers more from exposure to early deprivations, whereas boys' health is hit harder. Our findings highlight the importance of accounting for different dimensions of childhood deprivation, and they have strong policy implications for addressing inequality of opportunity.
Keywords: I32; R23; J11; 330; poverty; inequality; neighborhood effects; childhood; gender